IS THE STUDENTS’ SELF EFFICACY CORRELATED WITH STUDENTS’ PUBLIC SPEAKING ANXIETY? - Dwiyanti, Diza Aura; Fatimah Hidayahni Amin; Misnawaty Usman; Musdalifah; Nur Masthurah (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
This quantitative research investigates the correlation between self-efficacy and public speaking anxiety among students enrolled in the Business English Program. Data collection was conducted through a questionnaire to explore whether self-efficacy has a correlation with speaking anxiety in students and to identify the dominant aspect of self-efficacy. Results indicate a weak correlation between self-efficacy and public speaking anxiety, with no specific aspect of self-efficacy predominantly influencing speaking anxiety. Hence, it is crucial to note that correlation does not imply causation, and while a relationship exists, it does not firmly conclude that high self-efficacy directly reduces public speaking anxiety. Other factors might also contribute significantly to alleviate this anxiety.